Periodontal disease and periodontal bacteria as triggers for rheumatoid arthritis. Issue 1 (February 2017) - Cheng, Zijian; Meade, Josephine; Mankia, Kulveer; Emery, Paul; Devine, Deirdre A.
Abstract: There is an epidemiological association between periodontitis and rheumatoid arthritis (RA), which is hypothesised to lead to enhanced generation of RA-related autoantibodies that can be detected years before the onset of RA symptoms. Periodontitis is a common dysbiotic disease; tissue damage occurs because the immune system fails to limit both the resident microbial community and the associated local immune response. Certain periodontal bacteria, including Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans, may contribute to RA autoantibody production through direct post-translational modification of proteins or, indirectly, by influencing neutrophil-mediated neo-epitope generation. Oral bacteria that invade the blood may also contribute to chronic inflammatory responses and generation of autoantibodies. The putative association between periodontitis and the development of RA raises the potential of finding novel predictive markers of disease and disease progression and for periodontitis treatment to be included in the future as an adjunct to conventional RA immunotherapy or as part of a preventive strategy.